Peningkatan Kemampuan Menulis Anggota Kelompok Informasi Masyarakat Kota Malang Sebagai Upaya Melawan Hoaks, Disinformasi dan Misinformasi - Siswidiyanto, Siswidiyanto; Pratama, Muhammad Rizki; Galih, Aulia Puspaning; Pratama, Bayu Indra; Praja, Bayu Amengku (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2023)
At this time, society is faced with the flow of hoaxes, disinformation, and misinformation. Based on facts sourced from the 2021 Digital Literacy Survey by the Ministry of Communication and Informatics of the Republic of Indonesia, there is a tendency for people not to respond to existing hoaxes. Even though this hoax needs to be countered by counter-narratives with correct information. One way to fight it is to write. This service seeks to encourage an increase in the writing skills of Malang City Community Information Group (KIM) members to fight hoaxes, disinformation, and misinformation. The involvement of KIM has based on the premise that this element is a public institution to empower and improve the quality of public information according to their characteristics and needs. Devotion method in the form of writing training. The results of the dedication show that the participants are good at receiving writing training, as evidenced by the final average total of 3.99 which is included in the good category. However, more systemic and thematic training activities are still needed to improve sustainable writing skills.